2023
DOI: 10.1186/s12974-023-02703-2
|View full text |Cite
|
Sign up to set email alerts
|

Chronic kidney disease promotes cerebral microhemorrhage formation

Abstract: Background Chronic kidney disease (CKD) is increasingly recognized as a stroke risk factor, but its exact relationship with cerebrovascular disease is not well-understood. We investigated the development of cerebral small vessel disease using in vivo and in vitro models of CKD. Methods CKD was produced in aged C57BL/6J mice using an adenine-induced tubulointerstitial nephritis model. We analyzed brain histology using Prussian blue staining to exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 79 publications
0
8
0
Order By: Relevance
“…Elevated creatinine, indicative of impaired kidney function, has been increasingly recognized as a contributing factor to cerebrovascular pathologies. This relationship is supported by the study of Fang et al, which demonstrated that chronic kidney disease (CKD) promotes the formation of cerebral microhemorrhages, a key feature of CSVD ( 21 ). Furthermore, the systematic review and meta-analysis by Tang et al reinforce the association between kidney function and brain health, providing additional validation for our model's emphasis on creatinine levels ( 22 ).…”
Section: Discussionmentioning
confidence: 83%
“…Elevated creatinine, indicative of impaired kidney function, has been increasingly recognized as a contributing factor to cerebrovascular pathologies. This relationship is supported by the study of Fang et al, which demonstrated that chronic kidney disease (CKD) promotes the formation of cerebral microhemorrhages, a key feature of CSVD ( 21 ). Furthermore, the systematic review and meta-analysis by Tang et al reinforce the association between kidney function and brain health, providing additional validation for our model's emphasis on creatinine levels ( 22 ).…”
Section: Discussionmentioning
confidence: 83%
“…Together, these data strongly implicate pCS as a major contributory factor to the links between kidney failure and impaired brain function. Interactions of pCS with the peripheral vasculature have previously been reported, with evidence of arterial leakage in patients with CKD 46 and in animal 28 and in vitro models of uraemia 47 . Mechanistically, pCS at concentrations found in uraemia can cause interendothelial adherens junction disruption 46 , potentially underlying uraemia-associated endothelial leakage.…”
Section: Discussionmentioning
confidence: 93%
“…37 In the case of IVT, the hyperinflammatory state and disruption of the blood-brain barrier in CKD patients could impede the brain's capacity for effective tissue remodelling and neural repair, particularly impacting clot dissolution and reperfusion. 38 EVT's mechanical nature may pose unique challenges for CKD patients in comparison to IVT. The procedure's reliance on iodinated contrast agents, administered intravenously as opposed to intra-arterial administration, can worsen kidney dysfunction, potentially leading to contrast-induced nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…The biochemical buildup and inflammatory mediators stemming from CKD intensify the inflammatory response after a stroke, exacerbating endothelial dysfunction 37 . In the case of IVT, the hyperinflammatory state and disruption of the blood‐brain barrier in CKD patients could impede the brain's capacity for effective tissue remodelling and neural repair, particularly impacting clot dissolution and reperfusion 38 . EVT's mechanical nature may pose unique challenges for CKD patients in comparison to IVT.…”
Section: Discussionmentioning
confidence: 99%